Effects of the STCC eddies on the Kuroshio based on the 20-year JCOPE2 reanalysis results. (June 2015) - Chang, Yu-Lin; Miyazawa, Yasumasa; Guo, Xinyu
Highlights: Change of the Kuroshio transport is locally caused by eddy-forced mass convergence. The Kuroshio is generally stronger in eddy-rich years because of wind forcing. The nonuniform strengthening/weakening of Kuroshio are caused by eddies. Cold eddies lead to weaker PV jump, producing favorable conditions for intrusion. Abstract: In this study, 20 years of model reanalysis data are analyzed to study the effects of the subtropical countercurrent (STCC) eddies on the upstream Kuroshio, from east of Luzon to east of Taiwan. The effects are assessed from individual events to interannual time scales. The wind-driven Kuroshio is modified by the STCC eddies, with high spatiotemporal variations. The mass balance in the composite eddy events indicates that the strengthening and weakening of the Kuroshio transport are locally caused by the mass convergence and divergence produced by the eddies. The same analogy applies to the interannual time scale. In the eddy-rich years, the upstream Kuroshio is generally stronger because of wind forcing, yet the strengthening is nonuniform because of modification by the eddies. The larger number of warm eddies to the east of Taiwan and Luzon Island further strengthen the jet, whereas the larger number of cold eddies to the east of the Luzon Strait weaken the Kuroshio in the Luzon Strait. Drifter trajectories show larger Luzon Strait intrusion during the occurrence of cold eddies. The local weakening of the Kuroshio by cold eddies leads to a weaker potential vorticity jump, producing favorable conditions for the intrusion of a water mass into the South China Sea.